Lessons from the Ottoman Harem (on ethnicity, religion and war) - Murat Iyigun (Institute for the Study of Labor (IZA), 2008)
The Ottoman Empire had a profound impact in Europe, the Middle East and North Africa at the apogee of its power, covering the era between 1453 C. E. and 1699 C. E. In this paper, I exploit the empire's unique culture and institutions to examine the roles of ethnicity and religion in conflict and war. Based on one theory, the Ottoman conquests were driven by the Gaza ideology according to which the empire's central motivation was provided by a spirit of Holy War in the name of Islam. This is generally emphasized as the reason why the Ottomans initiated more conflicts in the West, and why on the eastern fronts, more conflicts were started by its rivals. Another not necessarily mutually exclusive theory claims that the Imperial Harem wielded considerable political power in Ottoman affairs. Accordingly, the members of the Harem with different ethnic or religious backgrounds often lobbied the Sultan to influence the geography of Ottoman conquests. Using comprehensive data on Ottoman wars and conflicts between 1401 C. E. and 1700 C. E., I document that Ottoman conquests were concentrated in the West throughout the mid-16th century. Then, I show that the ethnic background of Valide Sultan (the queen mother) was an important and independent determinant of whether the empire engaged in military conquests in Europe, North Africa or the Middle East. Depending on the empirical specification, the reign of a sultan with a European maternal genealogy was enough to offset more than 70 percent of the empire's western orientation in imperial conquests. Still, these findings do not rule out the possibility that the sultans' ethnic and cultural heritages - but not the politics of the queen mothers or their Harems - influenced Ottoman conquests.
urn:nbn:de:101:1-2008062558
Keywords: C72; 330; Conflict; religion; production and appropriation; family economics; Krieg; Geopolitik; Islam; Familie; Ethnische Gruppe; Interessenpolitik; Geschichte; Osmanisches Reich